Ascitic fluid amylase-to-serum amylase ratio to predict pancreatic duct leaks causing ascites - Wasserman, Reid (2024)
Objectives: Pancreatic duct leaks can cause ascites, and fluid amylase can be used as a marker to suggest pancreatic duct leak; however, there is no reference parameter or cutoff value for diagnosis. We assessed whether a novel ratio of ascitic fluid to serum amylase can reliably predict pancreatic leaks and need for endoscopic retrograde cholangiopancreatography (ERCP). Materials and methods: Patients who had fluid amylase from ascitic fluid and serum amylase within one week of confirmed pancreatic leaks via ERCP were included along with appropriate medical and surgical controls. Results: A total of sixteen patients were included in the study group. The mean ascitic fluid amylase to serum amylase ratio in the study group was 243, and 0.3511, and 0.9406 for medical and surgical controls respectively. The cutoff ratio to predict pancreatic leaks was 6.89 with 100% sensitivity and specificity (p-value 0.0000000000001347). Conclusions: Patients with a fluid to serum amylase ratio of at least 6.89 should be considered high risk for pancreatic leak with consideration to proceed directly to ERCP.